Social Media Management by the Sorong Regency Government in Maintaining its Image - I Prayoga; G E Liline (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the management of social media by the Sorong district government in maintaining its image as a developed district in West Papua by looking at various aspects such as the type of social media used, the content that is served and the purpose of publishing the content on social media. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques with in-depth interviews and non-participant observation and using purposive sampling technique in determining the informants. The results showed that the communication strategy of the Sorong district government in disseminating the government's work program through social networks was a strategy consisting of five planning stages, namely research, planning, implementation, measurement and reporting. The types of social media used are Facebook and Instagram. The information published on social media contains work programs that the Sorong district government has implemented to introduce these work programs to the community, hoping that the community will be able to evaluate all these work programs positively.